ONOMATOPE DALAM KOMIK MAHABHARATA - Elnadia Hutri Pertiwi; M. Nur Mustafa; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Basically, this study aims to describe the type and function of onomatopoeic comic Mahabharata. This study used a qualitative approach and descriptive method to describe the type and function of onomatopoeic comic Mahabharata. The results of the study and discussion of data acquisition: (1) In the comics Mahabharata, there are three types of onomatopoeic used in the comic. The types of onomatopoeic contained in the comics is a) onomatopoeic sound human, b) onomatopoeic sound of the animal, and c) other onomatopoeic sound. 2) function onomatope used in comics is a) expression functions b) exploration function.Keywords: onomatopoeia, comic, mahabharata